1997
DOI: 10.1063/1.119955
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low carbon concentrations on the electrical properties of highly boron doped SiGe layers

Abstract: We present results on the effect of carbon coevaporation by molecular beam epitaxy on electrical properties of highly boron doped SiGe:C layers for C concentration of around 1020 cm−3. Such C concentrations are needed for substantial suppression of boron outdiffusion. The concentration of electrically active boron and the hole mobility are not affected by the addition of carbon. Carbon-related defects, typically observed for C concentrations below the bulk solid solubility limit (<1018 cm−3), do not sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…These observations suggest that a surface accumulation layer of approximately 1ϫ10 12 during the boron doping, but that this is increasingly ''stabilized'' by growth interruption, so that only a fraction of it segregates to dope subsequently deposited material. The origin of this stabilization phenomenon could be the C or O containing impurities that have accumulated on the surface during interruption 13 -species which are known to inhibit boron diffusion, or due to some reconstruction of the accumulated boron, including clustering. In subsequent experiments we adopted a 40 min growth interruption 3-5 nm after growing doped layer as a compromise practical solution to minimize boron segregation.…”
mentioning
confidence: 99%
“…These observations suggest that a surface accumulation layer of approximately 1ϫ10 12 during the boron doping, but that this is increasingly ''stabilized'' by growth interruption, so that only a fraction of it segregates to dope subsequently deposited material. The origin of this stabilization phenomenon could be the C or O containing impurities that have accumulated on the surface during interruption 13 -species which are known to inhibit boron diffusion, or due to some reconstruction of the accumulated boron, including clustering. In subsequent experiments we adopted a 40 min growth interruption 3-5 nm after growing doped layer as a compromise practical solution to minimize boron segregation.…”
mentioning
confidence: 99%
“…This capturing should lead to the formation of carbon interstitial pairs, that could act as scattering or recombination centers, and thus influence charge carrier properties. In a recent publication, 4 we described some effects of carbon on the electrical properties of highly boron-doped SiGe:C layers for C concentration of around 10 20 cm Ϫ3 . We found no significant influence of carbon on charge carrier concentration and hole mobility.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, C does not reduce the electrical activity of boron. 4 The concentration of C in the investigated epitaxial layers exceeds the solid solubility limit by several orders of magnitude. 8 These C-rich layers form a metastable state with the majority of C atoms incorporated on substitutional sites.…”
Section: Resultsmentioning
confidence: 99%
“…C defects in Si have been studied in detail, and in particular the interactions of C with B to form a complex. 52,53 The large value of ⌽ Bp ϩ⌽ Bn has its origin in the high value of ⌽ Bp , and then could be connected to these defects with C in p-type B-doped layers. Moreover, recent investigations have also demonstrated that lateral inhomogeneities have to be taken into account to explain most of the experimental results on Schottky diodes, and in particular high values of the ideality factor.…”
Section: Fermi Level Position At Metal Interfaces With N-and P-type Smentioning
confidence: 99%